Gambaran Upaya Deteksi Dini dan Pencegahan Hipertensi - 05, Maulina; Nurdin, Ambia; Fitria, Ully; Dinen, Kiki Asrifa (Public Health Journal, 2024)
Hypertension is a health problem that is not only intense inthe world, but also in Indonesia. Hypertension is also referred to as the silent killer, which is a deadly disease without any signs and symptoms firstas a warning. The status of blood pressure will be higher as the function ofthe body's organs decreases. Hypertension is an abnormal increase in blood pressure which is the main cause of cardiovascular disease. The purpose of this study was to describe the efforts of early detection of hypertension and prevention of hypertension in Kayu Bawangvillage in the working area of Peat Public Health Center. Therefore, the public must be able to detect early and make efforts to prevent hypertension so that the blood pressure of people with hypertension can be controlled.